2017
DOI: 10.1155/2017/5898701
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Group of Escherichia coli Isolates from Broilers in Brazilian Poultry Slaughterhouse

Abstract: The aim of the study was to determine the phylogenetic groups of E. coli strains isolated from seemingly healthy broiler and broiler condemned suspected of colibacillosis in a Brazilian slaughterhouse. Samples from respiratory tract and edible giblets (liver and heart) of broilers with and without macroscopic lesions of colibacillosis were collected at slaughter. There were 84 strains isolated from broilers condemned of which 11 were obtained from swabs of the heart, 7 from the liver, and 66 from the respirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 33 publications
6
17
0
Order By: Relevance
“…Phylogenetic typing determines the genetic background or ancestry of an organism as well as differentiating between the pathogenic E. coli strains (B2 and D) from commensals (A and B1) [33,34]. Overall, phylogenetic analysis of APEC strains in this study revealed that majority belonged to Phylogenetic groups A and D. This is in agreement with several studies done elsewhere [20,28,35,36].…”
Section: Discussionsupporting
confidence: 91%
“…Phylogenetic typing determines the genetic background or ancestry of an organism as well as differentiating between the pathogenic E. coli strains (B2 and D) from commensals (A and B1) [33,34]. Overall, phylogenetic analysis of APEC strains in this study revealed that majority belonged to Phylogenetic groups A and D. This is in agreement with several studies done elsewhere [20,28,35,36].…”
Section: Discussionsupporting
confidence: 91%
“…Half of investigated isolates likely belong to group D, and are of lesser virulence. Phylogroups A and D were most frequently identified among our MDR E. coli isolates, similar to previous studies (Cortés et al, 2010;Coura et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Phylogenetic group A isolates were predominate in our study which considered healthy chicken. More often, phylogenetic group A E. coli isolates are commensal organisms, associated with healthy chicken, and rarely cause disease [ 20 , 21 ]. Our findings were in agreement with other workers [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…More often, phylogenetic group A E. coli isolates are commensal organisms, associated with healthy chicken, and rarely cause disease [ 20 , 21 ]. Our findings were in agreement with other workers [ 21 , 22 ]. Conversely, in birds with colibacillosis a majority of E. coli belongs to phylogenetic groups B2 [ 23 ].…”
Section: Discussionmentioning
confidence: 99%